Characterization of zeolite-based coatings for adsorption heat pumps - Freni, Angelo; Dawoud, Belal; Bonaccorsi, Lucio; Chmielewski, Stefanie; Frazzica, Andrea; Calabrese, Luigi; Restuccia, Giovanni (SpringerBriefs in Applied Sciences and Technology,, 2015)
This book proposes a radically new approach for characterizing thermophysical and mechanical properties of zeolite-based adsorbent coatings for Adsorptive Heat Transformers (AHT). It presents a developed standard protocol for the complete characterization of advanced coated adsorbers. Providing an in-depth analysis of the different procedures necessary for evaluating the performance of adsorbers, it also presents an analysis of their stability under the hydrothermal and mechanical stresses during their entire life cycle. Adsorptive Heat Transformers (AHT), especially adsorption chillers and heat pumps, are considered to be promising technologies to increase thermal energy efficiency. Nevertheless, an overall increase in performance of this apparatus is necessary for them to be considered a mature technology to be used commercially. Development of innovative coated adsorbers can be perceived as a key issue for the enhancement of AHT technology. This procedure relies on the deposition, either by means of a binder or by direct crystallization, of the adsorbent material over a metallic heat exchanger, aiming at the improvement of the heat transfer between the external heat source and the adsorbent itself. This book offers a valuable resource to those working on the development of novel adsorbent materials and advanced adsorbent beds for heating and cooling applications. It is also intended for researchers interested in renewable energy and energy efficiency. .